Domain-Specific Languages and Code Synthesis Using Haskell. - GILL, ANDY (Communications of the ACM, 2014)
The article discusses domain-specific languages and code synthesis using Haskell, which is said to be the premier pure functional programming language. Topics discussed include types in Haskell like those in other languages as constraining summaries of structural values, the influence of an embedded domain specific language (EDSL) on the cost of developing and maintaining a domain specific language when the facilities and tools of the host language are reused, and the additional functionality of the QuickCheck EDSL.